How Do Interpersonal Influences Shape Purchase Intentions for Online Services in Malang? The Mediating Role of Utilitarian and Hedonic Values - Jannah, Miftahul (Manajemen Multitalenta Indonesia, 2025)
To determine the interpersonal influence on perceived hedonic and utilitarian value through purchase intention on online food services in Malang city, this study was conducted. Students from Malang City who use online delivery services, became the sample for this quantitative study. The data of this study were collected through a Google Form questionnaire scored on a Likert scale. Data were collected from 100 respondents. The analysis tool used smart PLS analysis. The research findings show that: (1) interpersonal relationships significantly influence perceived utilitarian value; (2) interpersonal relationships do not significantly influence perceived hedonic value; (3) interpersonal relationships significantly influence purchase intention; and (4) perceived utilitarian value does not significantly influence purchase intention. (5) The impact of perceived hedonic value on purchase intention is quite large